Situational Crime Prevention (SCP) techniques to prevent and control cybercrimes: A focused systematic review. Issue 115 (April 2022) - Ho, Heemeng; Ko, Ryan; Mazerolle, Lorraine
Highlights: Evolution and developments of cybercrimes into cyber-focused and cyber-enabled crimes. Survey of research articles on the application of Situational Crime Prevention (SCP) techniques in preventing cybercrimes. Research gaps and future areas of research on SCP in cybercrimes. Abstract: Situational Crime Prevention (SCP) is a criminological approach that is shown to reduce crime opportunities drawing from five different strategies comprising 25 techniques. With the global increase in cybercrime, practitioners and researchers are increasingly investigating opportunities for applying SCP strategies and techniques to prevent cyber-focused and cyber-enabled crimes. Recent research proposes ways that SCP can be applied to cybercrime. Yet most of this research utilizes only a few of the SCP techniques and the linkages between the SCP techniques and opportunities for reducing cybercrimes are rarely made explicit. In this paper we evaluate the relevance of the full spectrum of SCP techniques to cybercrime and explicate how computer scientists, cybercrime and cybersecurity researchers and practitioners apply SCP principles to prevent and control cyber-enabled crime. Through a focused systematic review of 352 articles across computer science, criminal justice and criminology literature using the PRISMA method, this paper clarifies terminologies, explores the rise of cybercrimes, and explains the value of SCP for responding to cybercrimes. We provide a review of the current research undertaken to apply SCP to cybercrimes and conclude with a discussion on research gaps and potential future areas of research.